Prediction of the pull-out strength of chemical anchors in natural stone (Fracture and Structural Integrity, 2014)
The applicability of some numerical models for the prediction of the failure mechanism and of the bearing capacity of post-installed threaded rods chemically anchored in basalt, sandstone and limestone is investigated, as well as the reliability of theoretical formulations conceived for concrete. The numerical predictions, performed by means of engineering structural analysis software and advanced numerical codes, are compared with the results of an experimental research related to chemical anchors in natural stone. The minimum embedment depth for such fastening system is identified.
Keywords: Adhesive anchor